Desenvolvimento de um software de comunicação sem fio aplicado à instrumentação de unidade de elevação de petróleo tipo Plunger Lift - Oliveira, Felipe Denis Mendonça de (2009)
This dissertation aims to develop a software applied to a communication system for a wireless sensor network (WSN) for tracking analog and digital variables and control valve of the gas flow in artificial oil s elevation units, Plunger Lift type. The reason for this implementation is due to the fact that, in the studied plant configuration, the sensors communicate with the PLC (Programmable and Logic Controller) by the cables and pipelines, making any changes in that system, such as changing the layout of it, as well as inconveniences that arise from the nature of the site, such as the vicinity s animals presence that tend to destroy the cables for interconnection of sensors to the PLC. For software development, was used communication polling method via SMAC protocol (Simple Medium Access ControlIEEE 802.15.4 standard) in the CodeWarrior environment to which generated a firmware, loaded into the WSN s transceivers, present in the kit MC13193-EVK, (all items described above are owners of Freescale Semiconductors Inc.). The network monitoring and parameterization used in its application, was developed in LabVIEW software from National Instruments. The results were obtained through the observation of the network s behavior of sensors proposal, focusing on aspects such as: indoor and outdoor quantity of packages received and lost, general aspects of reliability in data transmission, coexistence with other types of wireless networks and power consumption under different operating conditions. The results were considered satisfactory, which showed the software efficiency in this communication system